Revealing non-crystalline polymer superstructures within electrospun fibers through solvent-induced phase rearrangements. Issue 36 (29th August 2019) - Morel, Alexandre; Oberle, Sophie C.; Ulrich, Sebastian; Yazgan, Gökçe; Spano, Fabrizio; Ferguson, Stephen J.; Fortunato, Giuseppino; Rossi, René M.
Abstract : Visualizing the inner architecture of electrospun nanofibers at a nanoscale level provides a detailed understanding of their formation process and the resulting mechanical properties. Abstract : The design of nanofibers for biomedical applications requires a deep understanding of the fiber formation process and the resulting internal structure. In this regard, non-crystalline, mesomorphic structures play a central role in the processing of many polymers as precursors in the formation of crystalline superstructures ( e.g. shish-kebab) and influence strongly the physical properties of polymers with a low degree of crystallinity. Yet, our ability to probe these relevant features is often greatly limited by their low contrast differences with the amorphous phase. We present an approach to reveal the organization of the mesomorphic superstructures within such polymeric materials, on the example of electrospun poly(l -lactide) nanofibers. Based on solvent-induced crystallization, this method employs fine-tuned solvent/non-solvent systems to enhance the contrast of these structural features by selectively triggering and controlling reorganization of the phases. Hereby, the mesomorphic regions are transformed into an α-crystalline phase, while the nanoscale spatial arrangement of the underlying superstructures is preserved. Combined with X-ray analytical techniques and electron microscopy, our approach provides detailed insights into the nanofiber's inner architecture, allowing for its direct visualization. Thereby, the influence of electrospinning parameters on the fiber formation process is explained as well as the impact of the resulting non-crystalline superstructures on single fiber mechanical properties. The method can be applied to comparable polymers for the development of materials with controlled, tailored properties.